2021
DOI: 10.3390/ijms22116119
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Response of Crop Plants towards Individual, Combined and Sequentially Occurring Abiotic Stresses

Abstract: In nature, plants are exposed to an ever-changing environment with increasing frequencies of multiple abiotic stresses. These abiotic stresses act either in combination or sequentially, thereby driving vegetation dynamics and limiting plant growth and productivity worldwide. Plants’ responses against these combined and sequential stresses clearly differ from that triggered by an individual stress. Until now, experimental studies were mainly focused on plant responses to individual stress, but have overlooked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 208 publications
0
26
0
Order By: Relevance
“…Environmental stresses, such as high temperatures and drought, adversely affect wheat viability and yield globally, especially during pollination and grain-filling stages. Plants have developed various morphological, physiological, biochemical and molecular alterations, and adaptation strategies to acquire stress tolerance [ 1 , 2 ]. One of the effective strategies is to transcriptionally regulate the expression of stress-related genes, among which transcription factors play a crucial role by activating and/or inhibiting specific genes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental stresses, such as high temperatures and drought, adversely affect wheat viability and yield globally, especially during pollination and grain-filling stages. Plants have developed various morphological, physiological, biochemical and molecular alterations, and adaptation strategies to acquire stress tolerance [ 1 , 2 ]. One of the effective strategies is to transcriptionally regulate the expression of stress-related genes, among which transcription factors play a crucial role by activating and/or inhibiting specific genes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the climate change scenario, lignocellulosic biorefinery could be strongly impacted since climate change has been described to affect biomass growth, productivity, chemical composition, and soil microbial community [ 1 , 107 , 108 , 109 , 110 ] ( Figure 5 ). Therefore, since the major feedstocks for lignocellulosic biorefinery are dedicated energy crops (e.g., switchgrass, Miscanthus giganteus , Guinea grass, energy cane, and others), or plant residues (e.g., sugarcane bagasse, corn (maize) stover, wheat straw, and others), climate change and the abiotic stress caused by them might significantly impact the production of cellulosic ethanol and other value-added commodities by reducing the yield and availability of these sources of biomass, along with changes in metabolic pathways.…”
Section: Challenges Of Biomass Utilization For Bioenergy In a Climate Change Scenariomentioning
confidence: 99%
“…Furthermore, recent evidence has shown that combined stresses might affect plant metabolism differently from isolated stress, showing unique responses [ 1 , 110 ]. As climate changes will be experienced as combined stresses, their effects under real field conditions must be studied.…”
Section: Challenges Of Biomass Utilization For Bioenergy In a Climate Change Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…Genomics-assisted breeding (GAB) allows to improve the germplasm [50]. Besides, multiple stress combinations can be studied [51]. Systems biology strategies are particularly interesting, implementing holistic approaches in these scenarios, integrating different -omics and bioinformatics tools [52].…”
Section: Functional Genomicsmentioning
confidence: 99%